2021
DOI: 10.3390/jimaging7090165
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection and Diagnosis of Diabetic Retinopathy: A Comprehensive Survey

Abstract: Diabetic Retinopathy (DR) is a leading cause of vision loss in the world. In the past few years, artificial intelligence (AI) based approaches have been used to detect and grade DR. Early detection enables appropriate treatment and thus prevents vision loss. For this purpose, both fundus and optical coherence tomography (OCT) images are used to image the retina. Next, Deep-learning (DL)-/machine-learning (ML)-based approaches make it possible to extract features from the images and to detect the presence of DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 161 publications
0
31
0
3
Order By: Relevance
“…This system diagnosis with two conventional 45-degree photographs of macular-centered and disc-centered and was reported to offer sufficient quality of detecting referable DR compared to human grading [ 16 ]. Many studies also reported high rate of sensitivity and specificity of autonomous-AI diagnosis system in diagnosing any stage of DR [ 38 , 90 , 91 , 92 , 93 , 94 , 95 ]. Diagnostic sensitivity of the algorithm (2iRetinex) for DR to sight threatening vision was examined, and the sensitivity is nearly identical to diagnosis by physician [ 92 ].…”
Section: Recent Topics In Imaging In Drmentioning
confidence: 99%
“…This system diagnosis with two conventional 45-degree photographs of macular-centered and disc-centered and was reported to offer sufficient quality of detecting referable DR compared to human grading [ 16 ]. Many studies also reported high rate of sensitivity and specificity of autonomous-AI diagnosis system in diagnosing any stage of DR [ 38 , 90 , 91 , 92 , 93 , 94 , 95 ]. Diagnostic sensitivity of the algorithm (2iRetinex) for DR to sight threatening vision was examined, and the sensitivity is nearly identical to diagnosis by physician [ 92 ].…”
Section: Recent Topics In Imaging In Drmentioning
confidence: 99%
“…Cataract grading involves comparing slit-lamp images to a set of standard photographs determined by a grading protocol such as LOCS III or WGS. Recent advancements in CAD techniques, which are defined as the subset of artificial intelligence (AI), are becoming more apparent in ophthalmology [27]. These advances have prompted other researchers to investigate alternative imaging modalities, including OCT and fundus images, for use in cataract grading.…”
Section: Automated Cataract Detection and Gradingmentioning
confidence: 99%
“…Detection of DR is performed in two steps: screening and diagnosis [26]. To prevent irreversible vision loss, screening for DR is essential to find the root causes that need prompt, thorough ocular examination and treatment.…”
Section: Screening and Diagnosis Of Drmentioning
confidence: 99%